ANALISIS PARTISIPASI MASYARAKAT SEMPADAN SUNGAI TAPIN DI KABUPATEN TAPIN TERHADAP KELESTARIAN LINGKUNGA - Nuruk Aina; Emmy Sri Mahreda; Kissinger Kissinger; Hamdani Fauzi (Lambung Mangkurat University-Indonesia, 2021)
The degradation of culture and people's lives leads to the degradation of rivers and water. An alarming condition regarding the declining quality of the river's ecology, which has occurred in many places. A lot of garbage is found in the river, the width of the river is getting shorter because on the river border many people's houses are built on the river, sand mining activities in the river erode the depth of the river so that it has an impact on the quality of river water, fish farming activities and so on. That phenomenon lead to decreasing quality of rivers. The purpose of writing this research is to analyze community participation in the river border towards the environmental sustainability of the Tapin river in Tapin Regency, South Kalimantan. This study used a mixed research method that combines quantitative and qualitative approaches with data collection techniques through interviews with informants, direct observations in the field and distributing questionnaires to respondents. The results showed that the value of community participation on participation in the Tapin River conservation effort was 70.825%, which means that it was included in the participation level of 62.50% - 81.24% declared